Tipping cascades between conflict and cooperation in climate change - J. Scheffran; W. Guo; F. Krampe; U. Okpara (Earth System Dynamics)
Following empirical research on the dynamics of conflict and cooperation under climate change, conditions, pathways, and societal responses in the climate–security nexus are analysed. Complex interactions between climate risks and conflict risks are connected to models of tipping points, compounding and cascading risks in the context of multiple crises. System and agent models of conflict and cooperation are considered to analyse dynamic trajectories, equilibria, stability, and chaos, along with adaptive decision rules in multi-agent interaction and related tipping, cascading, networking, and transformation processes. In particular, a bi-stable tipping model is applied to study transitions between conflict and cooperation, depending on internal and external factors and on multi-layered interaction networks of agents, showing how negative forces can reduce resilience to and induce collapse of violent conflict. The case study of Lake Chad is used for illustration to bridge disciplines and demonstrate climate change as a risk multiplier from a modelling perspective. These models relate to realities on the ground, where governance approaches and community behaviour can either lower or raise barriers to climate-induced conflict, exemplified by forced migration and militant forces lowering barriers and chances for cooperation. Adaptive and anticipative governance (AAG) based on integrative research and agency are discussed to prevent and contain climate-induced tipping to violent conflict and induce positive tipping towards cooperative solutions and synergies, e.g. through civil conflict transformation (CCT), environmental peacebuilding, and forward-looking policies for Earth system stability.